Lead-free composite soldering paste with high spreading rate and preparation method

By using lead-free solder powder and flux with specific ratios, a lead-free composite solder paste with high spread rate is prepared, which solves the problem that lead-free solder paste can easily lead to "false solder" and rosin residues during soldering, and improves the wetting, printing and corrosion resistance of the solder paste.

CN119525814AInactive Publication Date: 2025-02-28深圳市华远金属有限公司

Patent Information

Application Number
CN202411485815.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing lead-free solder paste is prone to "false soldering" during soldering, and the oxide and polymer residues caused by resin acid in rosin affect the brightness and spreadability of the solder joints, shortening the service life of electronic products.

Method used

Solder powders such as 95.4Sn3.1Ag1.5Cu, 96.5Sn3.0Ag0.5Cu, 98.5Sn1.0Ag0.5Cu or 99.0Sn0.3Ag0.7Cu and fluxes composed of modified rosin, activators, surfactants, thixotropic agents, thermosetting resins, antioxidants, corrosion inhibitors and organic solvents are used to uniformly mix the lead-free composite solder paste with high spreading rate through vacuum stirring.

Benefits of technology

It improves the wetting, printing and corrosion resistance of solder paste, reduces solder residues, reduces the incidence of welding defects, and extends the service life of electronic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098681600000041
    Figure BDA0005098681600000041
  • Figure BDA0005098681600000051
    Figure BDA0005098681600000051
  • Figure BDA0005098681600000071
    Figure BDA0005098681600000071
Patent Text Reader

Abstract

The invention belongs to the technical field of lead-free solder paste preparation, and discloses a lead-free composite solder paste with a high spreading rate and a preparation method. The lead-free composite soldering paste comprises soldering powder and soldering flux. The soldering flux is prepared from modified rosin, an activating agent, a surface active agent, a thixotropic agent, thermosetting resin, an antioxidant, a corrosion inhibitor and an organic solvent. The activating agent comprises hydroxy acrylic resin, terephthalic acid and ethylene bis stearamide. The prepared lead-free composite soldering paste is good in wettability, good in printability, low in corrosivity and less in residue, can effectively inhibit the occurrence of undesirable welding phenomena such as tin beads, dewetting and collapse, greatly reduces the reject ratio of printing, and improves the reliability of welding; the preparation method of the lead-free composite soldering paste is simple and easy to operate, raw materials are easy to obtain, and the lead-free composite soldering paste is suitable for industrial popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lead-free solder paste preparation, and in particular to a lead-free composite solder paste with a high spreading rate and a preparation method thereof. Background Art

[0002] Traditional solder paste is mainly made of lead-containing solder powder (such as lead-tin alloy solder powder), which has excellent welding and conductive properties. However, it is highly polluting to the environment. Long-term drinking of lead-contaminated water will lead to lead poisoning, which is seriously harmful to health. The alloys commonly used as lead-free solder powder are SnAgCu alloy, SnBi alloy, and SnZn alloy. However, compared with SnPb alloy solder powder, most lead-free solder powders are in a partially molten or solidified state during welding, which can easily lead to "cold solder joints", which is mainly caused by the poor wetting properties of lead-free solder powder.

[0003] In order to make lead-free solder powder achieve a similar welding effect as lead solder powder, more activators are usually added to remove the surface oxide film and reduce the surface tension between metals. At the same time, more rosin is added to protect the lead-free solder powder from being oxidized again during welding. However, the double bonds in the resin acid in rosin have strong chemical reactivity. The resin acid undergoes polymerization under the catalytic action, and the resulting oxide and polymer molecular chain segments are long and have poor fluidity. The residues remain on the surface of the solder joint, affecting the brightness of the solder joint and the spreadability of the solder paste, shortening the service life of the electronic product to a certain extent. The phenomenon of solder beads is prone to occur in the three processes of printing, patch and welding. Cold collapse occurs in the printing and patch process, and hot collapse occurs in the preheating and insulation stages of the welding process, resulting in solder beads in the final reflow soldering stage, and a high soldering defect rate. Summary of the invention

[0004] In order to solve the above technical problems, a lead-free solder paste with good spreadability, less solder paste residue, low corrosion and good anti-collapse performance is developed. The present application provides a lead-free composite solder paste with a high spreading rate and a preparation method.

[0005] In a first aspect, the present application provides a lead-free composite solder paste with a high spreading rate, comprising solder powder and flux in a weight ratio of 85-90:10-15; The solder powder is any one of 95.4Sn3.1Ag1.5Cu, 96.5Sn3.0Ag0.5Cu, 98.5Sn1.0Ag0.5Cu, and 99.0Sn0.3Ag0.7Cu; The soldering flux comprises the following raw materials in parts by weight: 20-35 parts of modified rosin, 12-20 parts of activator, 2-3 parts of surfactant, 3.5-5.5 parts of thixotropic agent, 4-6.5 parts of thermosetting resin, 1.5-2.5 parts of antioxidant, 3-6 parts of corrosion inhibitor and 30-50 parts of organic solvent; The activator comprises hydroxy acrylic resin, terephthalic acid and ethylene bis stearic acid amide in a weight ratio of 4-8:1-2:1-2.

[0006] By adopting the above technical scheme, hydroxy acrylic resin is used in the activator of the present application, and the polymerized monomer in the hydroxy acrylic resin includes acrylic acid, so that the prepared hydroxy acrylic resin contains an acrylic acid structure with a hydroxyl group. The electron-withdrawing effect of the hydroxyl group in the hydroxy acid makes its acidity stronger than that of the carboxylic acid, which can effectively remove metal oxides, and at the same time will not cause strong corrosion to the alloy powder in the solder powder. The tin ions and the pad form a good metallurgical bond to promote the wetting of the solder. Due to the electron-withdrawing effect of the methyl group in terephthalic acid, its acidity can also effectively remove metal oxides, and at the same time will not cause strong corrosion to the alloy powder in the solder powder. At the same time, in the present application, hydroxy acrylic resin, terephthalic acid and ethylene bis stearamide are compounded to enhance the fluidity of the welding residue, so that the flux paste using the present application has very little residue after welding and can be well spread around the solder joint, greatly reducing the corrosion of the residue to the solder joint and components.

[0007] Optionally, the preparation method of the hydroxyl acrylic resin includes the following steps: mixing hydroxyethyl methacrylate, a solvent and a polymerized monomer, heating to 70-90°C, adding a chain transfer agent and an initiator, and reacting for 2-3 hours to obtain a hydroxyl acrylic resin; the weight ratio of hydroxyethyl methacrylate, the polymerized monomer, the chain transfer agent, the initiator and the solvent is 10-15:20-30:2:0.5:50.

[0008] Optionally, the polymerizable monomers include 30 wt % or more of acrylic acid, and the polymerizable monomers further include one or more of methyl methacrylate, styrene and n-butyl acrylate.

[0009] Optionally, the chain transfer agent is mercaptoethanol.

[0010] Optionally, the initiator is azobisisobutyronitrile.

[0011] By adopting the above technical scheme, the hydroxy acrylic resin prepared by the above scheme has mild reaction conditions, is relatively clear, has good fluidity, and the prepared activator has good spreadability and fluidity in solder.

[0012] Optionally, the preparation method of the activator includes the following steps: weighing hydroxy acrylic resin, terephthalic acid and ethylene bisstearamide according to the mass ratio, transferring the three into an organic solvent, mixing and stirring evenly, heating to 120-150°C, and continuing to stir for 20 minutes; until the hydroxy acrylic resin, terephthalic acid and ethylene bisstearamide are completely dissolved in the organic solvent, cooling to room temperature under natural conditions to obtain an activator.

[0013] Optionally, the modified rosin is selected from one or more of fully hydrogenated rosin, disproportionated rosin, and polymerized rosin.

[0014] By adopting the above technical scheme, the modified rosin has good thermal stability and oxidation resistance. The carboxyl groups in the rosin can remove metal oxides at the welding temperature and protect the metal surface from oxidation. The formed organic film has good insulation and has the functions of moisture-proof and oxygen-isolating, thereby extending the service life of the welding spot.

[0015] Optionally, the thermosetting resin includes one or more of cyanate resin, melamine resin, furfural resin and furan resin.

[0016] By adopting the above technical scheme, the thermosetting resin in the soldering solder paste, such as the cyanate resin, can copolymerize with the hydroxy acrylic resin in the activator during the heating process when the soldering solder paste is prepared to generate a macromolecule with a highly cross-linked network structure, which has the characteristics of low hygroscopicity and can effectively avoid the problem of damage to the solder paste due to water absorption during storage, thereby effectively extending the service life of the solder paste; at the same time, copolymerization and cross-linking can also occur at the welding temperature, and the formed organic film has good insulation properties, has the functions of moisture-proof and oxygen-isolating, and extends the service life of the solder joint.

[0017] Optionally, the organic solvent comprises tetraethyl orthosilicate, N,N-dimethylacetamide and diethylene glycol butyl ether in a weight ratio of 2-3:1-5:1-2.

[0018] By adopting the above technical scheme, tetraethyl orthosilicate, N,N-dimethylacetamide and diethylene glycol butyl ether are compounded in the organic solvent in the present application, which can not only effectively dissolve and wet the flux material and provide a good ionization environment for the active substance, but also use co-solvents with different boiling points to form a wider boiling point range to adapt to the temperature changes of the entire welding process, so that the solder paste always remains in a liquid state during the welding process, maintains good fluidity and expansibility, and ensures the reliability of welding.

[0019] Optionally, the corrosion inhibitor comprises benzotriazole and triethylamine in a weight ratio of 1-1.5:1.

[0020] In a second aspect, the present application provides a method for preparing the above-mentioned lead-free composite solder paste with a high spreading rate, comprising the following steps: S1. Add surfactant, thixotropic agent, thermosetting resin, corrosion inhibitor and organic solvent into a reaction kettle, stir and dissolve them at 100-120°C, add modified rosin, activator and antioxidant after the solution is cooled to 70-80°C, stir evenly, and obtain flux; S2. Refrigerate the soldering flux at 2-10°C for 18-24 hours, return to room temperature, and grind with a three-roll grinder until the soldering flux particle size is 10-20 μm; S3. Place the solder powder and flux in a vacuum mixer according to a certain proportion and mix them evenly to obtain a lead-free composite solder paste.

[0021] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The lead-free composite solder paste prepared by the present application has good wettability, good printability, low corrosion, and little residue. It can effectively inhibit the occurrence of poor welding phenomena such as tin beads, dewetting, and collapse, greatly reducing the defective rate of printing and improving the reliability of welding. The lead-free composite solder paste prepared by the present application is stable in storage, has low hygroscopicity, has little corrosion to solder powder at room temperature, and can be stored for a long time.

[0022] 2. The preparation method of the lead-free composite solder paste in the present application is simple and easy to operate, and the raw materials are easily obtained, which is suitable for industrial promotion. DETAILED DESCRIPTION

[0023] The present application designs a lead-free composite solder paste with a high spreading rate, characterized in that it comprises solder powder and flux in a weight ratio of 85-90:10-15; the solder powder is any one of 95.4Sn3.1Ag1.5Cu, 96.5Sn3.0Ag0.5Cu, 98.5Sn1.0Ag0.5Cu, and 99.0Sn0.3Ag0.7Cu; The soldering flux comprises the following raw materials in parts by weight: 20-35 parts of modified rosin, 12-20 parts of activator, 2-3 parts of surfactant, 3.5-5.5 parts of thixotropic agent, 4-6.5 parts of thermosetting resin, 1.5-2.5 parts of antioxidant, 3-6 parts of corrosion inhibitor and 30-50 parts of organic solvent; The activator comprises hydroxy acrylic resin, terephthalic acid and ethylene bis stearic acid amide in a weight ratio of 4-8:1-2:1-2.

[0024] The lead-free composite solder paste with high spreading rate of the present application is prepared by the following method, comprising the following steps: S1. Add surfactant, thixotropic agent, thermosetting resin, corrosion inhibitor and organic solvent into a reaction kettle, stir and dissolve them at 100-120°C, add modified rosin, activator and antioxidant after the solution is cooled to 70-80°C, stir evenly, and obtain flux; S2. Refrigerate the soldering flux at 2-10°C for 18-24 hours, return to room temperature, and grind with a three-roll grinder until the soldering flux particle size is 10-20 μm; S3. Place the solder powder and flux in a vacuum mixer according to a certain proportion and mix them evenly to obtain a lead-free composite solder paste.

[0025] The technical problem solved by the present application is that a large amount of rosin is added to the existing lead-free solder paste to protect the lead-free solder powder from being reoxidized during welding, but the double bonds in the resin acid in the rosin have strong chemical reactivity, and the oxides and polymer molecular chains produced by the reaction are relatively long and have poor fluidity, which affects the spreadability and welding quality of the solder paste. In the present application, by using hydroxy acrylic resin in the activator, metal oxides can be effectively removed, and at the same time, strong corrosion will not be caused to the alloy powder in the solder powder. The prepared lead-free composite solder paste has good wettability, good printability, low corrosion, and less residue. It can effectively inhibit the occurrence of poor welding phenomena such as tin beads, dewetting, and collapse, and improve the reliability of welding.

[0026] The present application is further described in detail below in conjunction with specific embodiments.

[0027] Examples 1-5 Examples 1-5 are lead-free composite solder pastes made from different raw materials, the difference being that the flux ratios are different, as shown in Table 1.

[0028] Table 1 The activator used in Examples 1-5 is hydroxy acrylic resin, terephthalic acid and ethylene bis stearamide in a weight ratio of 5:1:2.

[0029] The preparation method of the hydroxy acrylic resin in the activator in Examples 1-5 comprises the following steps: Hydroxyethyl methacrylate, solvent and polymerized monomer are mixed, heated to 85°C, chain transfer agent and initiator are added, and reacted for 3 hours to obtain hydroxy acrylic resin; the weight ratio of hydroxyethyl methacrylate, polymerized monomer, chain transfer agent, initiator and solvent is 10:20:2:0.5:50. Among them, mercaptoethanol is used as chain transfer agent, azobisisobutyronitrile is used as initiator, and ethyl acetate is used as solvent.

[0030] The preparation method of the activator in Examples 1-5 comprises the following steps: The hydroxy acrylic resin, terephthalic acid and ethylene bisstearic acid amide are weighed according to the mass ratio, transferred into an organic solvent, mixed and stirred evenly, heated to 150° C., and stirred for 20 minutes; until the hydroxy acrylic resin, terephthalic acid and ethylene bisstearic acid amide are completely dissolved in the organic solvent, cooled to room temperature under natural conditions, and an active agent is obtained.

[0031] The thermosetting resin used in Examples 1-5 is a cyanate resin, specifically bisphenol M type cyanate, purchased from Jinjinle Chemical Co., Ltd.

[0032] The corrosion inhibitor used in Examples 1-5 is benzotriazole.

[0033] The surfactant used in Examples 1-5 is sodium dodecylbenzene sulfonate.

[0034] The thixotropic agent used in Examples 1-5 is fatty acid amide.

[0035] The antioxidant used in Examples 1-5 is the antioxidant BHT.

[0036] The organic solvent used in Examples 1-5 is tetraethyl orthosilicate, N,N-dimethylacetamide and diethylene glycol butyl ether in a weight ratio of 2:5:1.

[0037] The solder powder used in Examples 1-5 is 96.5Sn3.0Ag0.5Cu, model JHT-L305-HF10-T4, purchased from Shenzhen Jiahongtai New Materials Co., Ltd.

[0038] The method for preparing the lead-free composite solder paste in Examples 1-5 comprises the following steps: S1. Add surfactant, thixotropic agent, thermosetting resin, corrosion inhibitor and organic solvent into a reaction kettle, stir and dissolve them at 120°C, add modified rosin, activator and antioxidant after the solution is cooled to 80°C, stir evenly, and obtain flux; S2. Refrigerate the soldering flux at 2°C for 20 hours, return to room temperature, and grind with a three-roll grinder until the average particle size of the soldering flux particles is about 10 μm; S3. Place the solder powder and flux in a vacuum mixer according to a certain proportion and mix them evenly to obtain a lead-free composite solder paste.

[0039] Embodiment 6-8 Example 6 is based on Example 2, except that the solder powder used in Example 6 is 95.4Sn3.1Ag1.5Cu.

[0040] The method for preparing the lead-free composite solder paste in Example 6 comprises the following steps: S1. Add surfactant, thixotropic agent, thermosetting resin, corrosion inhibitor and organic solvent into a reaction kettle, stir and dissolve them at 120°C, add modified rosin, activator and antioxidant after the solution is cooled to 80°C, stir evenly, and obtain flux; S2. Refrigerate the solder flux at 5°C for 20 hours, return to room temperature, and grind with a three-roll grinder until the average particle size of the solder flux particles is about 10 μm; S3. Place the solder powder and flux in a vacuum mixer according to a certain proportion and mix them evenly to obtain a lead-free composite solder paste.

[0041] Example 7 is based on Example 2, except that the solder powder used in Example 7 is 98.5Sn1.0Ag0.5Cu.

[0042] S1. Add surfactant, thixotropic agent, thermosetting resin, corrosion inhibitor and organic solvent into a reaction kettle, stir and dissolve them at 120°C, add modified rosin, activator and antioxidant after the solution is cooled to 80°C, stir evenly, and obtain flux; S2. Refrigerate the soldering flux at 2°C for 20 hours, return to room temperature, and grind with a three-roll grinder until the average particle size of the soldering flux particles is about 10 μm; S3. Place the solder powder and flux in a vacuum mixer according to a certain proportion and mix them evenly to obtain a lead-free composite solder paste.

[0043] Example 8 is based on Example 2, except that the solder powder used in Example 8 is 95.4Sn3.1Ag1.5Cu.

[0044] The method for preparing the lead-free composite solder paste in Example 8 comprises the following steps: S1. Add surfactant, thixotropic agent, thermosetting resin, corrosion inhibitor and organic solvent into a reaction kettle, stir and dissolve them at 100°C, add modified rosin, activator and antioxidant after the solution is cooled to 70°C, stir evenly, and obtain flux; S2. Refrigerate the solder flux at 10°C for 24 hours, return to room temperature, and grind with a three-roll grinder until the average particle size of the solder flux particles is about 20 μm; S3. Place the solder powder and flux in a vacuum mixer according to a certain proportion and mix them evenly to obtain a lead-free composite solder paste.

[0045] Examples 9-10 Example 9 is based on Example 2, except that the organic solvent used in Example 9 is tetraethyl orthosilicate, N,N-dimethylacetamide and acetone in a weight ratio of 2:5:1.

[0046] Example 10 is based on Example 2, except that the organic solvent used in Example 10 is acetone, N,N-dimethylacetamide and diethylene glycol butyl ether in a weight ratio of 2:5:1.

[0047] Comparative Example 1 Comparative Example 1 is based on Example 2, except that the activator used in Comparative Example 1 is replaced by an equal amount of bisphenol M epoxy resin.

[0048] Performance Testing 1. The spreading rate and shear strength of the lead-free composite solder pastes prepared in Examples 1-10 and Comparative Example 1 were measured with reference to the standard "Test Method for Lead-Free Solder" of SJ / T11390-2009.

[0049] 2. The tin bead detection, viscosity and steel plate corrosion of the lead-free composite solder pastes prepared in Examples 1-10 and Comparative Example 1 were measured with reference to Japanese Standard JIS.Z.3284.

[0050] The measurement results are shown in Table 2.

[0051] Table 2 By analyzing the data in Table 2, it can be obtained that the solder pastes prepared in Examples 2, 6, 7 and 8 of the present invention have stronger comprehensive performance, the expansion rate (i.e., spreading rate) can be as high as 87.3%, the tin bead detection can reach level 1, the shear strength of the solder joints can have good performance, and the viscosity and steel plate corrosion can meet the standards, indicating that the new solder paste prepared in the embodiments of the present invention can have better application prospects than the traditional solder paste on the market.

[0052] In summary, the lead-free composite solder paste prepared in the present application has good wettability, good printability, low corrosiveness, and little residue. It can effectively inhibit the occurrence of poor welding phenomena such as tin beads, dewetting, and collapse, greatly reducing the defective rate of printing and improving the reliability of welding.

[0053] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A lead-free composite solder paste with high spreading rate, characterized in that: including solder powder and flux in a weight ratio of 85-90:10-15; The solder powder is any one of 95.4Sn3.1Ag1.5Cu, 96.5Sn3.0Ag0.5Cu, 98.5Sn1.0Ag0.5Cu and 99.0Sn0.3Ag0.7Cu; The soldering flux comprises the following raw materials in parts by weight: 20-35 parts of modified rosin, 12-20 parts of activator, 2-3 parts of surfactant, 3.5-5.5 parts of thixotropic agent, 4-6.5 parts of thermosetting resin, 1.5-2.5 parts of antioxidant, 3-6 parts of corrosion inhibitor and 30-50 parts of organic solvent; The activator comprises hydroxy acrylic resin, terephthalic acid and ethylene bis stearic acid amide in a weight ratio of 4-8:1-2:1-2.

2. The lead-free composite solder paste with high spreading rate according to claim 1, characterized in that: The preparation method of the activator comprises the following steps: Weigh hydroxy acrylic resin, terephthalic acid and ethylene bisstearic acid amide according to the mass ratio, transfer the three into an organic solvent, mix and stir evenly, heat to 120-150° C., and continue stirring for 20 minutes; until the hydroxy acrylic resin, terephthalic acid and ethylene bisstearic acid amide are completely dissolved in the organic solvent, cool to room temperature under natural conditions, and obtain an active agent.

3. The lead-free composite solder paste with high spreading rate according to claim 1, characterized in that: The preparation method of the hydroxy acrylic resin comprises the following steps: mixing hydroxyethyl methacrylate, a solvent and a polymerizable monomer, heating to 70-90° C., adding a chain transfer agent and an initiator, reacting for 2-3 hours, and obtaining the hydroxy acrylic resin; the weight ratio of hydroxyethyl methacrylate, the polymerizable monomer, the chain transfer agent, the initiator and the solvent is 10-15:20-30:2:0.5:

50.

4. The lead-free composite solder paste with high spreading rate according to claim 1, characterized in that: The polymerizable monomers include 30 wt % or more of acrylic acid, and the polymerizable monomers further include one or more of methyl methacrylate, styrene and n-butyl acrylate.

5. The lead-free composite solder paste with high spreading rate according to claim 1, characterized in that: The modified rosin is selected from one or more of fully hydrogenated rosin, disproportionated rosin and polymerized rosin.

6. The lead-free composite solder paste with high spreading rate according to claim 1, characterized in that: The thermosetting resin includes one or more of a cyanate resin, a melamine resin, a furfural resin, and a furan resin.

7. The lead-free composite solder paste with high spreading rate according to claim 1, characterized in that: The organic solvent comprises tetraethyl orthosilicate, N,N-dimethylacetamide and diethylene glycol butyl ether in a weight ratio of 2-3:1-5:1-2.

8. The lead-free composite solder paste with high spreading rate according to claim 1, characterized in that: The corrosion inhibitor comprises benzotriazole and triethylamine in a weight ratio of 1-1.5:

1.

9. A method for preparing a lead-free composite solder paste with a high spreading rate according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Add surfactant, thixotropic agent, thermosetting resin, corrosion inhibitor and organic solvent into a reaction kettle, stir and dissolve them at 100-120°C, add modified rosin, activator and antioxidant after the solution is cooled to 70-80°C, stir evenly, and obtain flux; S2. Refrigerate the soldering flux at 2-10°C for 18-24 hours, return to room temperature, and grind with a three-roll grinder until the soldering flux particle size is 10-20 μm; S3. Place the solder powder and the flux in a vacuum mixer according to a certain proportion and mix them evenly to obtain a lead-free composite solder paste.

Citation Information

Patent Citations

  • Lead-free soldering paste and preparation method thereof

    CN102489899A

  • Halogen-free cleaning-free rosin flux, and preparation and application thereof

    CN102513732A

  • Lead-free and halogen-free soldering paste for semiconductors

    CN104476016A

  • High-stability soldering flux paste

    CN106078002A

  • Solder paste scaling powder

    CN107931891A

Cited By

  • Double-ring air injection system for improving spreadability of CMT repair welding cast aluminum alloy and repair welding method

    CN121847906A